Use of hydrocolloids in meat systems - Strashynskyi, Igor; Omelchenko, Maksym; Karapalov, Anton (My University, 2020)
The most important ones of industrial importance and used in various branches of the food industry are as follows: locust bean gum, guar gum, tragacanth gum, konjac gum, gum arabic, karaya gum and tara gum. Knowing the properties of the ingredients, their correct selection and a clear choice of the ratio of the components will help to create complex mixtures of hydrocolloids with positive technological properties that are not inherent in individual compounds. They increase the viscosity of the system, reduce the effect of syneresis, increase elasticity will solve the most complex problems of industrial food production. Найважливіші з них промислового значення і використовуються в різних галузях харчової промисловості такі: камедь рожкового дерева, камедь гуару, камедь трагаканта, гумка коньяк, гуміарабік, камедь караї. Знання властивостей інгредієнтів, їх правильний підбір і чіткий вибір співвідношення компонентів допоможе створити складні суміші гідроколоїдів з позитивними технологічними властивостями, які не властиві окремим сполукам. Вони збільшують в'язкість системи, зменшують дію синерезису, підвищують еластичність, вирішують найскладніші проблеми виробництва промислової їжі.
Keywords: hydrocolloids; meat products; polysaccharides; гідроколоїди; м’ясні продукти; полісахариди; кафедра технології м’яса і м’ясних продуктів